Insulin degludec and insulin aspart: novel insulins for the management of diabetes mellitus. (November 2015) - Atkin, Stephen; Javed, Zeeshan; Fulcher, Gregory
Patients with type 2 diabetes mellitus require insulin as disease progresses to attain or maintain glycaemic targets. Basal insulin is commonly prescribed initially, alone or with one or more rapid-acting prandial insulin doses, to limit mealtime glucose excursions (a basal–bolus regimen). Both patients and physicians must balance the advantages of improved glycaemic control with the risk of hypoglycaemia and increasing regimen complexity. The rapid-acting insulin analogues (insulin aspart, insulin lispro and insulin glulisine) all have similar pharmacokinetic and pharmacodynamic characteristics and clinical efficacy/safety profiles. However, there are important differences in the pharmacokinetic and pharmacodynamic profiles of basal insulins (insulin glargine, insulin detemir and insulin degludec). Insulin degludec is an ultra-long-acting insulin analogue with a flat and stable glucose-lowering profile, a duration of action exceeding 30 h and less inter-patient variation in glucose-lowering effect than insulin glargine. In particular, the chemical properties of insulin degludec have allowed the development of a soluble co-formulation with prandial insulin aspart (insulin degludec/insulin aspart) that provides basal insulin coverage for at least 24 h with additional mealtime insulin for one or two meals depending on dose frequency. Pharmacokinetic and pharmacodynamic studies have shown that the distinct, long basal glucose-lowering action of insulin degludec and the prandial glucose-lowering effect of insulin aspart are maintained in the co-formulation. Evidence from pivotal phase III clinical trials indicates that insulin degludec/insulin aspart translate into sustained glycaemic control with less hypoglycaemia and the potential for a simpler insulin regimen with fewer daily injections.